2003
DOI: 10.1029/2002rs002861
|View full text |Cite
|
Sign up to set email alerts
|

Frequency‐and‐angular HF sounding and ISR diagnostics of TIDs

Abstract: A single digisonde, used as a receiver for ionospheric high frequency signals from broadcast stations, was able to determine the wave characteristics of traveling ionospheric disturbances (TIDs) using frequency shift and arrival angle measurements. During a measurement campaign, aimed at recovering large‐scale wave‐like processes in the upper atmosphere, in March 2001 at the MIT Haystack Observatory (Millstone Hill, MA), a Digisonde Portable Sounder (DPS) made simultaneous observations with the incoherent scat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 10 publications
1
28
0
Order By: Relevance
“…The obtained results concerning the LS structure agree with theoretical indications of ST effects (Cot and Teitelbaum, 1980;Somsikov, 1983Somsikov, , 1987Somsikov and Ganguly, 1995;Dungenbaeva and Ganguly, 2004;Antonova et al, 2006) and do not contradict the experimental results obtained by Mishin et al (1991), Beley et al (1995), and Galushko et al (1998Galushko et al ( , 2003. In particular, these results confirm the conclusion by Galushko et al (1998) that ST-generated AGWs can be observed at sunrise better than at sunset (corresponding data will be presented in future publications).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The obtained results concerning the LS structure agree with theoretical indications of ST effects (Cot and Teitelbaum, 1980;Somsikov, 1983Somsikov, , 1987Somsikov and Ganguly, 1995;Dungenbaeva and Ganguly, 2004;Antonova et al, 2006) and do not contradict the experimental results obtained by Mishin et al (1991), Beley et al (1995), and Galushko et al (1998Galushko et al ( , 2003. In particular, these results confirm the conclusion by Galushko et al (1998) that ST-generated AGWs can be observed at sunrise better than at sunset (corresponding data will be presented in future publications).…”
Section: Discussionsupporting
confidence: 81%
“…The great variety of ST-linked phenomena in the atmosphere has resulted in a number of studies being carried out on the analysis of ionosphere parameter variations obtained by different methods of ionosphere sounding (Bezrodny and Yampolski, 1976;Popov and Yampolski, 1981;Galushko and Yampolski, 1983;Mishin et al, 1991;Drobzhev et al, 1992;Bezotosnyi et al, 1994;Beley et al, 1995;Sobral et al, 1997;Galushko et al, 1998;Hocke and Igarashi, 2002;Galushko et al, 2003). However, virtually all experimental data were obtained using indirect methods for analyzing the spectrum of ionosphere parameter variations, which can result from a number of factors.…”
Section: Introductionmentioning
confidence: 99%
“…Kotake et al 2006;Hernández-Pajares, Juan, & Sanz 2006). They can be generated by auroral sources at the high latitude thermosphere, the passage of the solar terminator (Galushko et al 2003), and storms, hurricanes, and tornados in the troposphere. Detailed information about the sources, energetics, and scale sizes of energy coupling from the lower atmosphere to the upper atmosphere, along with resulting ionospheric effects, is critical to developing a deep understanding of overall upper atmospheric energy balance.…”
Section: Travelling Ionospheric Disturbancesmentioning
confidence: 99%
“…Representing the ionosphere by a moving undulated mirror facilitates relating the measured signal parameters to the characteristics of the propagating waves using the Doppler‐FAS technique (Beley et al, ; Galushko et al, ; Paznukhov et al, ). While the time series of all signal characteristics { ρ ( t ), δ ( t ), ε ( t ), and β ( t )} vary with the wave period T Ω , the Doppler frequency variation δ( t ) proved to be the most reliable indicator for the detection of quasi‐sinusoidal variations.…”
Section: Tid Model and The Fas Techniquementioning
confidence: 99%